Why don't UK citizens protest against privacy-invading dragnet surveillance?. (10th October 2016) - Renaud, Karen; Flowerday, Stephen; English, Rosanne; Volkamer, Melanie
Abstract : Purpose: The purpose of this study was to identify to identify reasons for the lack of protest against dragnet surveillance in the UK. As part of this investigation, a study was carried out to gauge the understanding of "privacy" and "confidentiality" by the well-informed. Design/methodology/approach: To perform a best-case study, the authors identified a group of well-informed participants in terms of security. To gain insights into their privacy-related mental models, they were asked first to define the three core terms and then to identify the scenarios. Then, the participants were provided with privacy-related scenarios and were asked to demonstrate their understanding by classifying the scenarios and identifying violations. Findings: Although the participants were mostly able to identify privacy and confidentiality scenarios, they experienced difficulties in articulating the actual meaning of the terms privacy, confidentiality and security. Research limitations/implications: There were a limited number of participants, yet the findings are interesting and justify further investigation. The implications, even of this initial study, are significant in that if citizens' privacy rights are being violated and they did not seem to know how to protest this and if indeed they had the desire to do so. Practical implications: Had the citizens understood the meaning of privacy, and their ancient right thereto, which is enshrined in law, their response to the Snowden revelations about ongoing wide-scale surveillance might well have been more strident and insistent. Originality/value: People in the UK, where this study was carried out, do not seem to protest the privacy invasion effected by dragnet surveillance with any verve. The authors identify a number of possible reasons for this from the literature. One possible explanation is that people do not understand privacy. Thus, this study posits that privacy is unusual in that understanding does not seem to align with the ability to articulate the rights to privacy and their disapproval of such widespread surveillance. This seems to make protests unlikely.